The Concept of Ma‘rifatullah in the Sufism of Divine Love in the Second Hijri Century: A Study of the Thought of Rabi‘ah al-‘Adawiyah - Anir Syam Azisyah; Nurlaelah Abbas; Mahmuddin M (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze the concept of ma'rifatullah in the Sufi thought of Rabi'a al-Adawiyya and to situate it within the development of Sufism in the second century Hijri. Rabi'a is regarded as an important figure who introduced divine love as the foundation of the relationship between a servant and Allah, at a time when early Sufism was predominantly characterized by asceticism based on fear and hope. This research employs a qualitative method with a library research approach, using data sources such as works on Sufi thought, biographies of Rabi'a al-Adawiyya, and other relevant scholarly literature. Data analysis is conducted through a descriptive-analytical method by interpreting Rabi'a’s ideas within the socio-intellectual context of Basrah and the dynamics of early Sufism. The findings indicate that ma'rifatullah according to Rabi'a is grounded in mahabbah, namely pure, sincere, and unconditional divine love that transcends motives of fear of punishment and hope for reward. This concept marks an important shift in Sufism from an ascetic orientation toward a Sufism of love. In conclusion, the thought of Rabi'a al-Adawiyya made a significant contribution to the development of Sufism through the purification of spiritual orientation, the affirmation of divine love as the highest spiritual station, and the strengthening of the inner dimension in the experience of knowing Allah.